Evaluation of Hepatitis A Seroprevalence in Kastamonu Province, Turkey - TÜFEKCİ, Enis Fuat; ÇALIŞIR, Büşra; YAŞAR DUMAN, Melike; KILINÇ, Çetin (Medical Records - International Medical Journal, 2022)
Aim: Hepatitis A disease is a contagious liver infection caused by the hepatitis A virus (HAV). This study aimed to decide the hepatitis A seroprevalence in all age groups in Kastamonu province, Turkey. Material and Method: The current study analyzed the anti-HAV antibodies test results of the patients who applied to Kastamonu Training and Research Hospital for various reasons between 2018-2022. The most up-to-date test results of patients sent more than one serum sample were evaluated. The patients were separated into eight age groups: 0-10,11-20, 21-30, 31-40, 41-50, 51-60, 61-70, and ≥71. The anti-HAV IgM and anti-HAV IgG values were determined using the chemiluminescence microparticle immunoassay method in the Abbott Architect i2000SR. The results were evaluated based on the manufacturer’s instructions. Results: There was positivity in 27 (1.3%) of 2083 patients in whom anti-HAV IgM was studied and in 837 (58.2%) of 1439 patients in whom anti-HAV IgG was studied. The anti-HAV IgG positivity in females and males was 55.9% and 61.0%, respectively; anti-HAV IgM positivity was 1.7% and 0.8%. The anti-HAV IgG positivity rate increased with increasing age (p
Keywords: 3. Good health